2016
DOI: 10.1111/bjso.12146
|View full text |Cite
|
Sign up to set email alerts
|

Direct and extended intergenerational contact and young people's attitudes towards older adults

Abstract: Research suggests that positive intergenerational contact can improve young people's attitudes towards older adults. However, today's age‐segregated society may not provide ample opportunities for positive contact between younger and older adults to occur on a regular basis. In three studies, we investigated whether the positive attitudinal outcomes associated with direct contact might also stem from a more indirect form of intergenerational relationship: extended contact. In Study 1 (N = 70), extended contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 67 publications
6
81
2
4
Order By: Relevance
“…The findings are consistent with research showing that intergenerational contact [29] and intergenerational programmes [27], [10] can have a positive impact on impressions of older people. In the case of the current research, an intergenerational education programme boosted perceptions of older people as being 'warm', thus confirming a commonly held positive age stereotype [24].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings are consistent with research showing that intergenerational contact [29] and intergenerational programmes [27], [10] can have a positive impact on impressions of older people. In the case of the current research, an intergenerational education programme boosted perceptions of older people as being 'warm', thus confirming a commonly held positive age stereotype [24].…”
Section: Discussionsupporting
confidence: 92%
“…Research shows that intergenerational contact reduces negative attitudes and stereotypes about older adults [29], [30], [31], [32]; including the stereotype that older adults are incompetent [33]. However, it is possible that when the task or context of intergenerational contact highlights or confirms negative old age stereotypes, especially those around dependency or incompetence, this may increase rather than decease stereotypes in this area.…”
Section: Digital Technology As a Negatively Stereotyped Contextmentioning
confidence: 99%
“…However, their article does not provide specific research data except Bousfield and Hutchison's (2010) study, which was performed with older students (16-25 years old) and interrogated their contacts with the elderly in general without probing the grandparents-grandchildren relationships. A positive impact of direct and indirect contacts of young adults with older people on ageism has recently been confirmed by studies performed in the United Kingdom (Drury, Hutchison, & Abrams, 2016).…”
Section: Contacts With Grandparentsmentioning
confidence: 75%
“…However, research on intergroup contact has demonstrated that the quality of the interaction (i.e. positive or negative) with outgroup members is a stronger predictor of attitudes towards the outgroup, compared to frequency (Drury, Hutchison, & Abrams, ).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%